New combinations and a new name in Bletia (Bletiinae; Orchidaceae) - Sosa, Victoria; Chase, Mark W. (Phytotaxa, 2020)
New combinations and names are proposed for species formerly placed in three genera of subtribe Bletiinae. Based on the latest phylogenetic analyses of the subtribe in which species of Basiphyllaea and Hexalectris were embedded among the species of Bletia, twelve new combinations and a new name are proposed in the last.